PENAHANAN ANAK ANGGOTA GENK MOTOR PELAKU TINDAK PIDANA BERDASARKAN PERSPEKTIF PERLINDUNGAN ANAK - Azzanu Asyari Ohara (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Abstract Children represent next router of a state and nation generation, therefore children needs construction and special attention. Nowadays government has try to gave protection to Indonesian children by publishing various regulation wich formulating protectionto children who deal with law, but unorfunately, detention to children who deal with special case like